The Greek secret she carries - Roscoe, Pippa (Harlequin presents, 2021)
"When Summer Soames landed in Athens, she wanted to find a missing piece of her past...yet found combustible chemistry with enigmatic Theron Thiakos instead! Just as quickly as their intense fling started, it dramatically imploded...and Summer was firmly shut out of his life. Now rumors bring Theron to Summer's doorstep to discover her shocking pregnancy is as obvious as the still-sizzling desire between them! He's determined to give their child the family unit he lost. But Summer's trust isn't easily won...and Theron's secrets aren't easily shared..." -- Page [4] cover.